Adenovirus 12 E1A gene detection by polymerase chain reaction in both the normal and coeliac duodenum. Issue 9 (September 1994) - Lawler, M; Humphries, P; O'Farrelly, C; Hoey, H; Sheils, O; Jeffers, M; O'Briain, D S; Kelleher, D
Abstract : A 12 amino acid sequence from the adenovirus 12 E1B protein is homologous at the protein level with a similar 12-mer derived from the wheat protein A-gliadin. It has been suggested that exposure to Ad 12 could sensitise individuals to gliadins with resultant gluten sensitive enteropathy. In this study, the polymerase chain reaction (PCR) was used to analyse duodenal biopsy tissue from patients with coeliac disease for the presence of Ad 12. The sensitivity of the assay system was at least 1 in 10(5) cells and specificity was confirmed both by probing with an internal oligonucleotide and by direct sequencing. Ad 12 sequences were detected in three of 17 patients with adult coeliac disease and in five of 16 adult controls with normal duodenal biopsies. Since exposure to the virus would be predicted to occur in infancy we also studied patients with childhood coeliac disease diagnosed at less than 1 year of age. Ad 12 was positive in three of 10 childhood coeliac patients and one of seven controls. In addition, we studied a cohort of patients who presented with a diarrhoeal illness and associated anti alpha gliadin antibodies in 1983. These patients had duodenal biopsies performed at this time. One of three patients with abnormal histology had detectable Ad 12 while two of 14 with normal findings were positive for Ad 12. Finally, the potential oncogenic nature of Ad 12 prompted examination of a group of patients with intestinal tumours. Ad 12 DNA was, however, in only two of 19 tumour samples tested. These data indicate that Ad 12 can be successfully detected using PCR on paraffin embedded tissue. Furthermore, Ad 12 was detected at a relatively high level in normal duodenum. The results do not, however, support the hypothesis that prior exposure to Ad 12 is implicated in the pathogenesis of coeliac disease.